2021
DOI: 10.1007/s42979-021-00785-4
|View full text |Cite
|
Sign up to set email alerts
|

Deep Transfer Learning-Based Framework for COVID-19 Diagnosis Using Chest CT Scans and Clinical Information

Abstract: The Coronavirus Disease 2019 (COVID-19) which first emerged in Wuhan, China in late December, 2019, has now spread to all the countries in the world. Conventional testing methods such as the antigen test, serology tests, and polymerase chain reaction tests are widely used. However, the test results can take anything from a few hours to a few days to reach the patient. Chest CT scan images have been used as alternatives for the detection of COVID-19 infection. Use of CT scan images alone might have limited capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…In this study, the VGG-19 and DesNet-169 models were ensembled, and the authors claimed that this ensemble model showed better results than the other existing models for the case of five datasets, including three datasets of CT scan images and two datasets of X-ray images. Another study [ 17 ] proposed an ANN-based framework for the fast and automatic detection of patients infected by COVID-19. A study by Mukherjee et al [ 18 ] claimed that if multiple data types were integrated, then more information could be found, which might be helpful in detecting the anomaly patterns of COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the VGG-19 and DesNet-169 models were ensembled, and the authors claimed that this ensemble model showed better results than the other existing models for the case of five datasets, including three datasets of CT scan images and two datasets of X-ray images. Another study [ 17 ] proposed an ANN-based framework for the fast and automatic detection of patients infected by COVID-19. A study by Mukherjee et al [ 18 ] claimed that if multiple data types were integrated, then more information could be found, which might be helpful in detecting the anomaly patterns of COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Secondly, RT-PCR tests are limited in availability and require considerable time. Deep learning (DL), a subset of AI, plays a dynamic role in controlling the outbreak of the virus infection, not only by detecting the presence of the virus during the early stages but also by enhancing the public health care system and analyzing the virus for appropriate medications and vaccination [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. To identify the presence of abnormalities in the lung, DL can be used for the reconstruction and segmentation of chest X-rays or CT scans [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of pretrained DL models is prevalent in COVID-19 imaging tools. For example, commonly used models are AlexNet, VGGNet-XX, GoogleNet, ResNet-XX, Xception, Inception, wideResNet, MobileNet, NASNet, DarkNet, CheXNet, ShuffleNet, Incep-tionResNetV2, InceptionV3 (to name a few) [62,67,79,95,102,103,111,112,114,115,121,125,128,134,139,143,146,[151][152][153]158,159,162,210,211,213,214,220,234,247,249,255,263,270,274,277,284]. We found a total of 10 articles; among them, the researchers of 9 articles used conventional augmentation techniques such as resizing, zooming, gaussian noise, blur, spatial transformation, contrast adjustment, flipping, scaling, cropping, rotation, intensity transformation [69,71,75,84,85,92,93,96,…”
Section: Transfer Learningmentioning
confidence: 99%
“…They reported that the proposed model AUC value is more than 80% on most test sides. Mishra et al [128] used a deep learning algorithm to diagnose COVID-19. The authors also worked on finding ANN's severity index of covid infection.…”
mentioning
confidence: 99%
“…Deep learning, a representative technique of artificial intelligence (AI), has shown great promise for detecting some common diseases based on clinical images, especially in medical image-related disease diagnosis and outcome prediction ( 11 ). Deep learning techniques have been utilized in image recognition of thoracic tumors ( 12 ).…”
Section: Introductionmentioning
confidence: 99%